Monopole Antenna On Transparent Substrate And Rectifier For Energy Harvesting Applications In 5G - Azam, S. M. Kayser; Islam, Md. Shazzadul; Hossain, A K M Zakir; Othman, Mohamadariff (Science and Information Organization, 2020)
In line with the harvested energy required for the emerging 5G technology, this article proposes a planar monopole antenna and a rectifier. The proposed Coplanar Waveguide (CPW)-fed antenna is printable on a transparent Poly-Ethylene Terephthalate (PET) substrate. The antenna has a center frequency at 3.51 GHz within a bandwidth of 307 MHz that covers the pioneer 5G band in Malaysia. The designed omnidirectional antenna exhibits the maximum gain of 1.51 dBi with a total efficiency of 95.17 percent. At the antenna frequency, a rectifier has been designed with the voltage doubler technique on a Rogers RO3003 substrate. Over an input RF power of 0 dBm, the rectifier has a power conversion efficiency around 42 percent. The proposed antenna rejects harmonics at least until 16 GHz frequency that makes it compatible with the rectifier to eliminate an additional bandpass filter or impedance matching network from the energy harvesting system.